Transforming Asian cities intellectual impasse, Asianizing space, and emerging trans-localities - Perera, Nihal; Tang, Wing-shing.; T&F eBooks (Milton Park, Abingdon, Oxon ; New York, N.Y. : Routledge, 2013)
"Draws attention to how Asians produce their contemporary urban practices, identities and spaces as part of, resisting, responding to and avoiding larger global and national processes. The individual chapters illustrate that "global" spaces are more (trans)local, traditional environments are more modern, and Asian spaces are better defined than acknowledged. The aim is to develop room for understandings of Asian cities from Asian standpoints, especially acknowledging how Asians observe, interpret, understand, and create space in their cities"--Publisher's description.
1. Seoul : a Korean capital / Sharon Hong -- 2. Rajadamnoen Avenue : Thailand's transformative path towards modern polity / Koompong Noobanjong -- 3. Public art, urban renewal, and the construction of a national history : the Revive Manila program and the new Manileño campaign / Tessa Maria Guazon -- 4. An unexpected urban renewal practice : the emergence of a multicultural historic plaza in Taipei / Huey-Jiun Wang -- 5. Critical vernacularism : multiple roots, cascades of thought, and the local production of architecture / Nihal Perera -- 6. Housing rights and citizenship of rural migrants in urban China : the case of Yuanhenong, Shanghai / Zhao Yeqin -- 7. Ordinary lives in extraordinary Cyberabad / Diganta Das -- 8. Street vending in Indonesian cities : their characteristics and activities in Yogyakarta / Deden Rukmana and Djarot Purbadi -- 9. Perceptions of tenure security in a squatter settlement in Lahore, Pakistan / Fatima Wajahat -- 10. The struggle for living space : ethnicity, housing, and the politics of urban renewal in Japan's squatter areas / Takuya Motooka and Toshio Mizuuchi -- 11. Contests over community : a community organization in Hong Kong / Hon-Chu Leung -- 12. Traversing the city : some gendered questions of access in Mumbai / Shilpa Phadke -- 13. Indianizing the neighborhood unit : the Jawahar Nagar plan / Sanjeev Vidyarti -- 14. Planning and self-organizing : the case of small towns in Sri Lanka / Jagath Munasinghe -- 15. Niche authority in urbanized villages : bottom-up codetermination in megacity developments in China / Sonia Schoon.
Includes bibliographical references (p. [262]-284) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Cities and towns -- Asia; Sociology, Urban -- Asia; Electronic books